Identification And Parasitization Of Parasitoids Against Setothosea Asigna In Oil Palm Plantations In Dharmasraya District, Indonesia - Zahlul Ikhsan; Hidrayani Hidrayani; Willy Friddo Sianturi; Sholih Kurniawati; Aulia Oktavia; Erise Anggraini (Jurnal Riset Perkebunan, 2023)
Setothosea asigna poses a significant threat to oil palm plantations, necessitating effective control measures. This survey-based research, utilizing Purposive Sampling, identifies parasitoids and evaluates their effectiveness in Dharmasraya oil palm plantations, a crucial palm oil-producing region in Indonesia. The selected criteria encompass plantations aged 6-15 years with a considerable Setothosea asigna infestation, providing a comprehensive overview of the pest's impact. The study establishes five sample points diagonally, each comprising five randomly chosen plants, totaling 25 samples per site, ensuring diverse representation. The predominant larval parasitoids exhibit noteworthy efficacy, primarily from the Hymenoptera order, Braconidae family, Genus Apanteles, and Spinaria. Among the 110 larvae observed, five were parasitized, resulting in the emergence of 65 parasitoids. The parasitization rate varies from 0 - 9.09%, with prominent contributions from Apanteles sp. and Spinaria sp., belonging to the endoparasitoid type. This research significantly contributes to sustainable agriculture practices and the palm oil industry, offering insights into targeted pest control for Setothosea asigna. Despite its focus on Dharmasraya, the study provides a valuable foundation for broader applications and invites further research for generalization.